THE ROLE OF DIGLOSSIA IN EDUCATION: CHALLENGES AND OPPORTUNITIES - Siti Munawaro; Dewi Nurfatimah; M. Saiful Azhar; M. Joeanda Riski (Al-Irsyad: Journal of Education Science, 2025)
Diglossia is a phenomenon in sociolinguistics that means the use of two language variants with different social functions, where the two language variants are divided into high language (H) and low language (L). This has a significant impact in education, where initial observations found a comprehension gap in bilingual students. This article aims to explore the role of diglossia in an educational context, focusing on the challenges and opportunities it raises in the teaching and learning process. This research uses a qualitative approach with literature study methods and interviews with educators and students in one of the Islamic boarding schools in Batang Hari who experience the phenomenon of diglossia. The collected data were analyzed descriptively to identify the role of diglossia in understanding teaching materials, as well as strategies that can be applied to minimize communication barriers in the teaching and learning process. The results of the study show that diglossia can function as a language enrichment tool, but it can also lead to gaps in understanding if not managed with the right strategy.